(untitled) (Scientific journal of the Fergana State University, 2023)
In the settlements of the Jizzakh oasis, you can find many traditions and customs associated with the wedding, in particular the wedding, and the bride and groom. The customs and rituals associated with marriage and wedding ceremony are almost the same as in most other regions. In many places, the traditional "fatiha oshi", "sarpo yuborish", "maslahat to‘yi", "qudalar to‘yi", "haitlik", "girls’ party", "padar oshi" or "chimildik yigi" held after the wedding are still practiced", "Bows of bride", "Kelin kordi" traditions are held.